Storytelling Visualization as an Approach to Designing a Creative Industry Map of West Sumatra - Tedy Wiraseptya; Maharian Agung (LPPM Institut Pendidikan Nusantara Global, 2026)
West Sumatra's creative industry is growing rapidly and demonstrating a strategic role in strengthening the culture-based economy. However, this complex creative ecosystem has not been comprehensively mapped through informative and communicative visual media. This research aims to design elements of a West Sumatra creative industry map using a storytelling visualization approach, a method that combines data, narrative, and visual elements to produce a more meaningful representation of information. Furthermore, this study applies digital imaging isometric art techniques as a design approach to create more structural, detailed, and readable map visuals, and utilizes Artificial Intelligence (AI) as a finishing tool to refine graphic elements. The research method is carried out through the stages of literature data collection, isometric visual design, and AI-based graphic refinement. The results show that the integration of storytelling visualization with isometric art can improve the clarity of information structure, strengthen the Minangkabau cultural narrative, and provide a more immersive visual experience for users. The use of AI has proven effective in accelerating the visual refinement process without eliminating the character of manual design. This research contributes to the development of creative mapping methods based on visual narratives and offers a new design model that can be applied to creative mapping contexts in other regions.